Interaction of exercise bioenergetics with pacing behavior predicts track distance running performance - Kirby, B. S.; Winn, B. J.; Wilkins, B. W.; Jones, A. M. (Journal of Applied Physiology, 2021)
The best possible finishing time for a runner competing in distance track events can be estimated from their critical speed (CS) and the finite amount of energy that can be expended above CS (D´). During tactical races with variable pacing, the runner with the "best" combination of CS and D´ and, therefore, the fastest estimated finishing time prior to the race, does not always win. We hypothesized that final race finishing positions depend on the relationships between the pacing strategies used, the athletes` initial CS, and their instantaneous D´ (i.e., D´ balance) as the race unfolds. Using publicly available data from the 2017 International Association of Athletics Federations (IAAF) World Championships men`s 5,000-m and 10,000-m races, race speed, CS, and D´ balance were calculated. The correlation between D´ balance and actual finishing positions was nonsignificant using start-line values but improved to R2 > 0.90 as both races progressed. The D´ balance with 400 m remaining was strongly associated with both final 400-m split time and proximity to the winner. Athletes who exhausted their D´ were unable to hold pace with the leaders, whereas a high D´ remaining enabled a fast final 400 m and a high finishing position. The D´ balance model was able to accurately predict finishing positions in both a "slow" 5,000-m and a "fast" 10,000-m race. These results indicate that although CS and D´ can characterize an athlete`s performance capabilities prior to the start, the pacing strategy that optimizes D´ utilization significantly impacts the final race outcome.